Modeling of Border Irrigation in Soils with the Presence of a Shallow Water Table. I: The Advance Phase - Sebastián Fuentes; Carlos Chávez (Agriculture, 2022)
The overelevation of the water table in surface irrigation plots is one of the main factors affecting salinization in agricultural soils. Therefore, it is necessary to develop simulation models that consider the effect of a shallow water table in the process of advance-infiltration of the water in an irrigation event. This paper, the first in a series of three, develops a simple mathematical model for the advance phase of border irrigation in soils with the presence of a shallow water table. In this study, the hydrodynamic model of the Barré de Saint-Venant equations is used for the water surface flow, and the equations are solved using a Lagrangian finite-differences scheme, while in the subsurface flow, an analytical solution for infiltration in soils with a shallow water table is found using the bisection method to search for roots. In addition, a hydraulic resistance law is used that eliminates the numerical instabilities presented by the Manning–Strickler law. The model results for difference irrigation tests show adjustments with an R2 > 0.98 for the cases presented. It is also revealed that, when increasing the time step, the precision is maintained, and it is possible to reduce the computation time by up to 99.45%. Finally, the model proposed here is recommended for studying the advance process during surface irrigation in soils with shallow water tables.